Surface Laser Processing of Additive Manufactured 1.2709 Steel Parts: Preliminary Study - O. Černašėjus; J. Škamat; V. Markovič; N. Višniakov; S. Indrišiūnas (Advances in Materials Science and Engineering)
Recently, metal selective laser sintering (SLS) techniques have attracted lively interest as a promising technology, which offers a number of unique applications in manufacturing of metal parts with complex internal structure and geometry. However, unsatisfactory surface properties of as-manufactured SLS parts cause high cost of finish processing and restrict wider application of SLS products. The paper presents results of the study, which was taken to evaluate capability of laser processing to improve surface quality of SLS parts manufactured from powder maraging steel 1.2709 (X3NiCoMoTi 18-9-5). The properties of processed surfaces were assessed, and the main dependencies of the roughness, hardness, wear resistance, and phase composition on the main parameters of laser processing—scanning speed, laser power, and number of processing times—were determined. The roughness of surfaces was diminished up to ∼41%, the hardness was increased up to ∼88%, and the wear resistance was improved up to almost 4 times, as compared with surface of as-manufactured SLS part. The preliminary study has demonstrated that laser processing has considerable potential for improvement of surface conditions of steel additive manufactured parts.